ANALISIS KARAKTERISASI TOKOH UTAMA DALAM FILM BARBIE OF SWAN LAKE (2003) - Rondonuwu, Tesa Helly; Wantasen, Isnawati L.; Rattu, Jultje A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis study aimed to analyze the character development of the main character in the film Barbie of Swan Lake (2003), directed by Owen Hurley, which was written by Elana Lesser and Cliff Ruby, and produced by Kim Dent Wilder and Rob Hudnut. This film tells about a kind girl who want to makes the revolution. She has development in character. The identified data are analyzed according to the intrinsic approach Edgar V. Roberts (1983) in Writing Themes About Literature to identified and analyzed the main character. In describing the character development used the approach by Rene Wellek and Austin Warren (1976) in Theory of Literature. This research shows about characterization of the main character and the character development of the main character in the film is influenced by situation, human’s idea, and words. This research shows the meaningful characterization and development of the main character in film Barbie of Swan Lake (2003).Key words : Character development, film, Barbie of Swan Lake (2003).